Comprehensive research of the distribution of tellurium-bismuth mineralization in the ores of the Abyz and Maleevskoe sulfide deposits (Republic of Kazakhstan) - Anastasia N. Nikolaeva; Alexey K. Mazurov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2024)
Abstract. Within the formations of ensimatic and ensialic island arcs in the territory of Central and Northern Kazakhstan, there are more than thirty pyrite deposits enriched in copper, lead, zinc, gold, silver and rare metal mineralization, which is still insufficiently studied. Relevance. The need to replenish information on tellurium-bismuth mineralization in ores of sulfide deposits formed in ensimatic (Abyz deposit) and ensialic (Maleevskoe deposit) island-arc systems, to establish a spatial connection of this type of mineralization with geodynamic conditions and predict the potential for their associated extraction from ore. Aim. To study and compare morphological characteristics, distribution patterns and conditions for the formation of tellurium-bismuth mineralization in ores of pyrite deposits formed in different island-arc geodynamic settings. Methods. Inductively coupled plasma mass spectrometry, mineragraphic and mineralogical analyses, scanning electron microscopy in combination with X-ray spectral microanalysis, Raman spectroscopy, thermobarogeochemical studies. Results. A comparison of the pyrite deposits of the Rudno-Altai and Chingiz-Tarbagatai island arc systems showed many similarities and differences between them. The deposits have a multi-stage formation and a similar mechanism of ore deposition with similar physicochemical conditions for the formation of tellurium-bismuth mineralization. A spatial relationship between Te-Bi mineralization and geodynamic settings was established: for deposits associated with paleooceanic structures, a predominance of the tellurium element is observed, and for continental rifts, a predominance of the bismuth element.